Answer:
-1&0, 0&1 and 2&3
Explanation:
Given the quadratic expression f(x) = x2 – 3x + 1, the real zero of the expression will be the roots of the equation and this can be gotten as shown below
f(x) = x² – 3x + 1
On factorizing the equation using the general fomula when f(x) = 0;
x = -b±√b²-4ac/2a
from the equation above, a = 1, b = -3, c = 1
x = -(-3)±√(-3)²-4(1)(1)/2(1)
x = 3±√9-4/2
x = 3±√5/2
x = (3+√5)/2 or x = (3-√5)/2
x = 2.62 and 0.38
since 2.62 is between 2&3 and 0.38 is between 0&1 and -1&0, the required answer will be -1&0, 0&1 and 2&3